Secondary battery and electric equipment
By regulating the particle distribution density and porosity in the positive electrode active layer, the problem of poor circulation stability of high-nickel positive electrode materials when increasing the energy density is solved, and the high energy density, fast charging performance and long cycle life of the battery are achieved.
Patent Information
- Application Number
- CN202411865204.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-16
AI Technical Summary
While increasing the energy density, the existing high-nickel layered oxide positive electrode materials lead to a decrease in electrochemical activity and a deterioration in cycle stability, thereby shortening the cycle life of the battery.
By regulating the distribution density of the first active particles and the second active particles in the positive electrode active layer, and matching the positive electrode and negative electrode active layers with appropriate porosity, the secondary battery meets a specific Z value range, ensuring that the battery is suppressed under high pressure conditions, the electrolyte is fully infiltrated, and the lithium ion diffusion rate is increased.
The high energy density, good fast charging performance and long cycle life of the battery are achieved, and the problems of particle breakage and cycle stability of the positive electrode material under high pressure conditions are avoided.
Smart Images

Figure BDA0005194893720000111 
Figure BDA0005194893720000121 
Figure BDA0005194893720000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] The cathode material is one of the key components of lithium-ion batteries and can largely determine the energy density of the battery. Among them, high-nickel layered oxide cathode materials are widely used in the field of electric vehicles due to their high specific capacity, high voltage platform and high compaction density. However, even the energy density of high-nickel layered oxide cathode materials is difficult to meet the increasing demand for the range of power batteries.
[0003] At present, the energy density of positive electrode materials is mainly improved by high nickel content or high voltage. However, for high nickel content, as the nickel content in the positive electrode material increases, the nickel located in the octahedron tends to enter the lithium site in the lattice, resulting in a decrease in the electrochemical activity of the positive electrode material. For high voltage, while achieving high energy density, cracking problems will occur due to lattice collapse, gas release or structural reconstruction, that is, high nickel content or high voltage will lead to poor cycle stability of the positive electrode material, resulting in a shorter cycle life of the battery. Therefore, it is urgent to develop an effective means to enable the battery to maintain high energy density while having good fast charging performance and long cycle life. Summary of the invention
[0004] The object of the present invention is to overcome the deficiencies of the prior art and provide a secondary battery and an electrical device.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a secondary battery, the secondary battery comprising a positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active layer disposed on the surface of the positive electrode current collector, the positive electrode active layer comprising a positive electrode active material; the negative electrode sheet comprising a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector, the negative electrode active layer comprising a negative electrode active material;
[0007] The secondary battery satisfies: 0.14≤Z≤4.67;
[0008] Where Z = (n1 / n2)*(p1 / p2);
[0009] n1 / 10000μm 2 is the distribution density of the first active particles in the cross section of the positive electrode active layer, the first active particles being particles of the positive electrode active material particles having a size greater than or equal to 8 μm;
[0010] n2 pieces / 10000 μm 2 is the distribution density of the second active particles in the cross-section of the positive electrode active layer, and the second active particles are particles smaller than 8 μm in the positive electrode active material particles;
[0011] p1 is the porosity of the positive electrode active layer;
[0012] p2 is the porosity of the negative electrode active layer.
[0013] As an embodiment of the present invention, the secondary battery satisfies: 1.24 ≤ Z ≤ 2.43.
[0014] As an embodiment of the present invention, the volume ratio of the first active particles to the second active particles in the unit volume of the positive electrode active layer is 1:(0.3 - 0.6).
[0015] As an embodiment of the present invention, n1 / n2 satisfies: 0.3 ≤ n1 / n2 ≤ 7.
[0016] As an embodiment of the present invention, the secondary battery satisfies at least one of the following:
[0017] a. n1 is 8 - 36;
[0018] b. n2 is 6 - 25;
[0019] c. p1 is 20% - 30%;
[0020] d. p2 is 35% - 45%.
[0021] As an embodiment of the present invention, the negative electrode sheet satisfies at least one of the following:
[0022] e. The particle size D of the negative electrode active material v50 is 3 - 12 μm;
[0023] f. The tap density of the negative electrode active layer is 1.4 - 1.8 g / cm 3 .
[0024] As an embodiment of the present invention, the positive electrode active material includes a core and a shell layer provided on the surface of the core; the core includes a compound with the chemical formula Li 1+a [Ni x Co y Mn z M b O2; wherein, 0.5 ≤ x < 1, 0 < y < 0.3, 0 ≤ z < 0.3, -0.1 ≤ a < 0.2, 0 < b < 0.3, and x + y + z + b = 1; M includes at least one of Ti, Zr, Sr, Sb, Nb, Ru, Pd, Y, Ce, and W.
[0025] As an embodiment of the present invention, the content of cobalt element increases gradually from the center of the inner core to the surface of the inner core.
[0026] As an embodiment of the present invention, the shell layer includes a metal oxide, and the metal element X in the metal oxide includes at least one of Al, W, Ca, Ce, Ti, Zr, and Y.
[0027] As an embodiment of the present invention, the shell layer satisfies: 2500≤w*h≤16500; wherein w ppm is the content of the metal element X in the positive electrode active material, and h nm is the thickness of the shell layer.
[0028] In a second aspect, the present invention provides an electrical device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electrical device.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention regulates the distribution density of the first active particles (particles greater than or equal to 8 μm in the positive electrode active material particles) and the second active particles (particles less than 8 μm in the positive electrode active material particles) in the positive electrode active layer, and matches a positive electrode active layer with a suitable porosity and a negative electrode active layer with a suitable porosity, so that 0.14≤Z≤4.67, Z=(n1 / n2)*(p1 / p2) is satisfied. This can not only effectively inhibit the particle breakage of the positive electrode active material under high pressure conditions to maintain the high energy density of the battery and improve the cycle performance of the battery; it can also make the electrode plate fully infiltrated with the electrolyte to reduce polarization and increase the diffusion rate of lithium ions, so that the secondary battery has high energy density while having good fast charging performance and long cycle life. DETAILED DESCRIPTION
[0031] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0032] According to a first aspect of the present invention, a secondary battery is provided, the secondary battery comprising a positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active layer disposed on the surface of the positive electrode current collector, the positive electrode active layer comprising a positive electrode active material; the negative electrode sheet comprising a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector, the negative electrode active layer comprising a negative electrode active material;
[0033] The secondary battery satisfies: 0.14≤Z≤4.67;
[0034] Where Z = (n1 / n2)*(p1 / p2);
[0035] n1 / 10000μm 2 is the distribution density of the first active particles in the cross section of the positive electrode active layer, the first active particles being particles of the positive electrode active material particles having a size greater than or equal to 8 μm;
[0036] n2 / 10000μm 2 is the distribution density of the second active particles in the cross section of the positive electrode active layer, wherein the second active particles are particles smaller than 8 μm in the positive electrode active material particles;
[0037] p1 is the porosity of the positive electrode active layer;
[0038] p2 is the porosity of the negative electrode active layer.
[0039] The present invention regulates the distribution density of the first active particles (particles greater than or equal to 8 μm in the positive electrode active material particles) and the second active particles (particles less than 8 μm in the positive electrode active material particles) in the positive electrode active layer, and sets a positive electrode active layer with a suitable porosity and a negative electrode active layer with a suitable porosity, so as to satisfy 0.14≤Z≤4.67, Z=(n1 / n2)*(p1 / p2). This can not only effectively inhibit the particle breakage of the positive electrode active material under high pressure conditions to maintain the high energy density of the battery and improve the cycle performance of the battery, but also enable the positive electrode plate and the negative electrode plate to be fully infiltrated with the electrolyte to reduce polarization and increase the diffusion rate of lithium ions, so that the secondary battery has high energy density while having good fast charging performance and long cycle life.
[0040] Optionally, the value of the above Z can be specifically one of 0.14, 0.50, 1.02, 1.22, 2.45, 2.50, 3.30, 3.80, 4.67 or any two of the range values; the above secondary battery includes at least one of a wound soft-pack battery, a wound aluminum shell battery, a wound cylindrical battery, a laminated soft-pack battery, a laminated aluminum shell battery, etc.; the negative electrode active material in the negative electrode sheet of the secondary battery includes at least one of a carbon-based material, a silicon-based material, and a tin-based material.
[0041] Optionally, in order to further optimize the fast charging performance and long cycle life of the battery, the value of Z is 1.24 to 2.43.
[0042] As an embodiment of the present invention, the volume ratio of the first active particles to the second active particles in the unit volume of the positive electrode active layer is 1:(0.3-0.6). Optionally, the volume ratio of the first active particles to the second active particles in the unit volume of the positive electrode active layer can be a range value of one or any two of 1:0.3, 1:0.4, 1:0.5, 1:0.6. The volume ratio of the first active particles to the second active particles in the positive electrode active layer is within the above range, which can improve the compaction density of the positive electrode sheet while ensuring that the pores of the positive electrode sheet are within a suitable range, and further optimize the compressive strength and energy density of the positive electrode sheet.
[0043] As an embodiment of the present invention, the n1 / n2 satisfies: 0.3≤n1 / n2≤7. Optionally, the n1 / n2 can be specifically a range value of one or any two of 0.3, 0.8, 1.5, 2.3, 3, 4, 5, 6, 7. When the value of n1 / n2 is within the above range, it can ensure that the material system has a better size particle grading effect, improve the compaction density of the positive electrode sheet while ensuring dynamic performance, and reasonable size particle grading makes the number of gaps between particles small at the same time, which can play a beneficial effect of reducing the contact resistance between particles, reducing the internal resistance and polarization of the battery, shortening the lithium ion transmission distance, and helping to improve the battery capacity and rate performance. Reasonable grading can ensure that the positive electrode active material particles have strong compressive strength under high compaction density, reduce the cracking phenomenon caused by stress concentration of the positive electrode active material particles during rolling and cyclic charge and discharge, thereby reducing the exposed area of the active site, reducing the contact side reaction with the electrolyte, and achieving the effect of improving the battery cycle performance.
[0044] As an embodiment of the present invention, the n1 is 8 to 36; optionally, the n1 can be a range of one or any two of 8, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, and 36. Studies have found that when n1 is 8 to 36, the positive electrode active material has a suitable specific surface area, which is beneficial to the performance of the battery.
[0045] As an embodiment of the present invention, n2 is 6 to 25; optionally, n2 can be specifically a range of one or any two of 6, 8, 10, 12, 14, 16, and 25. Studies have found that when n2 is 6 to 25, the number of small-sized particles in the battery system can be ensured to be moderate. On the one hand, it can ensure that a sufficient number of small particles can improve the dynamic performance of the positive electrode sheet, while controlling it within a certain upper limit, so that the number of small particles will not be too large, resulting in a reduction in the compaction density of the positive electrode sheet, thereby ensuring that the battery system has a higher energy density.
[0046] As an embodiment of the present invention, the p1 is 20% to 30%; optionally, p1 can be specifically a range of one or any two of 20%, 22%, 24%, 26%, 28%, and 30%. The porosity of the positive electrode active material layer is related to the particle size, particle distribution, particle morphology, proportion of the positive electrode active material, and the rolling process of the electrode sheet. The appropriate porosity is conducive to the infiltration of the electrolyte and reduces the diffusion energy of the lithium ion deintercalation process. When p1 is 20% to 30%, it is conducive to the rapid infiltration of the electrolyte into the positive electrode sheet and ensures that lithium ions are easier to deintercalate.
[0047] As an embodiment of the present invention, the p2 is 35% to 45%; p2 can be specifically 35%, 37%, 39%, 41%, 43%, 45% or any two of them. Studies have found that when p2 is 35% to 45%, it is beneficial for the electrolyte to quickly infiltrate the positive electrode sheet and ensure that lithium ions are easier to deintercalate.
[0048] In some embodiments, the particle size D of the negative electrode active material v50 3~12μm;
[0049] In some embodiments, the compaction density of the negative electrode active layer is 1.4 to 1.8 g / cm 3 .
[0050] Optionally, the particle size D of the negative electrode active material v50 Specifically, it can be 3 μm, 5 μm, 7 μm, 9 μm, 12 μm or any two of them. v50 When the nanostructured carbon nanotubes are 3 to 12 μm, the channels for lithium ion embedding and extraction are shorter, which is conducive to quickly reaching a fully embedded lithium state, thereby having better charge and discharge performance.
[0051] Optionally, the compaction density of the negative electrode active layer can be 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 The study found that when the compaction density of the negative electrode active layer is 1.4-1.8 g / cm 3 It is beneficial to the wettability of the electrolyte and also makes the battery have a higher energy density.
[0052] As an embodiment of the present invention, the positive electrode active material includes a core and a shell layer arranged on the surface of the core, wherein the core includes a chemical formula of Li 1+a [Ni x Coy Mn z M b Compounds of ]O2; wherein, 0.5 ≤ x < 1, 0 < y < 0.3, 0 ≤ z < 0.3, -0.1 ≤ a < 0.2, 0 < b < 0.3, and x + y + z + b = 1; M includes at least one of Ti, Zr, Sr, Sb, Nb, Ru, Pd, Y, Ce, and W. It has been found that when choosing the compound with the above chemical formula as the core of the positive electrode active material, the positive electrode active material has a high specific capacity per gram while having high long-term cycle stability. In some embodiments, 0.8 < x < 9.5, that is, the nickel content in the positive electrode active material accounts for more than 80% of the transition metal elements, and the nickel content is greater than 80%, making the positive electrode active material have a high specific capacity, which is beneficial to improving the energy density of the battery.
[0053] As an embodiment of the present invention, the shell layer includes a metal oxide, and the metal element X in the metal oxide includes at least one of Al, W, Ca, Ce, Ti, Zr, and Y. The metal oxide coating layer can improve the cycle stability, safety of the battery, and reduce the material cost.
[0054] In some embodiments, the content of cobalt in the positive electrode active material increases from the center of the core to the surface of the core. When the content of cobalt is distributed from the center of the core to the surface of the core in an increasing trend, the Co element can improve the electronic conductivity of the material, and can also reduce the degree of cation mixing and occupation, thereby enhancing the structural stability and rate performance of the material. The surface Co element content is higher, which can improve the surface kinetic performance of the material and the structural stability of the surface, and help to improve the capacity. At the same time, the higher surface Co content also means a lower surface Ni content, which can reduce the occurrence of side reactions between highly active Ni4+ and the electrolyte during charging and discharging, and improve the long-term cycle performance of the battery system. The distribution of cobalt elements on the surface and inside of the particles in the positive electrode active material can be prepared by using a cross-section polisher (e.g., IB-09010CP argon ion cross-section polisher of JEOL, Japan); then refer to JY / T010-1996, use a scanning electron microscope (e.g., Sigma 300 scanning electron microscope of ZEISS, Germany) to scan the cross section of the positive electrode active material; then use inductively coupled plasma emission spectroscopy (ICP) for detection. The ratio of the mass of the cobalt element in the surface region (the region extending 0.05L from the edge of the particle in the cross-sectional image to the inside, L refers to the major axis length of the positive electrode active material particle) in the cross-sectional image of the obtained positive electrode active material to the mass of the total cobalt element in the cross-sectional image of the obtained positive electrode active material is taken as the ratio of the mass of the cobalt element in the surface region of the positive electrode active material to the total mass of the cobalt element in the positive electrode active material. In this way, the distribution of the cobalt element in the positive electrode active material can be obtained.
[0055] In some embodiments, the shell layer also includes non-metallic oxides, such as boron oxide, silicon dioxide, etc. The metal oxide is used as the shell material to prevent excessive contact between the electrolyte and the core, reduce the occurrence of side reactions, thereby improving the battery cycle stability, inhibiting gas production, and improving safety performance.
[0056] As an embodiment of the present invention, the shell layer satisfies: 2500≤w*h≤16500; wherein w ppm is the content of the metal element X in the positive electrode active material, and h nm is the thickness of the shell layer. Optionally, the w*h can be specifically a range value of one or any two of 2500, 5000, 7500, 10000, 12500, 15000, and 16500. When the content of the metal element X in the positive electrode active material and the thickness of the shell layer satisfy the above relationship, the coating layer provided on the surface of the positive electrode active material can be kept with a suitable and uniform thickness. The particles on the surface of the positive electrode active material are covered by the provided coating layer, which can act as a physical barrier, protect the positive electrode active material from the erosion of the electrolyte, and inhibit the occurrence of side reactions. The coating layer with suitable thickness can promote the rotor of the interface ion charge, improve the interface dynamics, and improve the battery performance. When the w*h value is within the above range, it can protect the core of the positive electrode active material from being corroded by the electrolyte, while taking into account the migration rate of lithium ions during the deintercalation process.
[0057] In a second aspect, the present invention provides an electrical device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electrical device.
[0058] In order to clearly understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0059] Example 1
[0060] The present embodiment provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator (PE separator) and an electrolyte (1 mol / L LiPF6 solution, the solvent being composed of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1); a preparation method thereof comprises the following steps: stacking the positive electrode sheet, the negative electrode sheet and the separator sheet in order, placing the separator between the positive and negative electrode sheets, and winding to obtain a bare battery cell; then placing the bare battery cell in an outer packaging aluminum-plastic film, baking to remove moisture, injecting an electrolyte, and vacuum packaging to obtain a secondary battery.
[0061] 1) The above-mentioned positive electrode sheet is prepared by the following preparation method:
[0062] S1, adding nickel sulfate, manganese sulfate, cobalt sulfate and deionized water into a first reaction kettle and mixing them evenly (wherein the molar ratio of elements Ni:Co:Mn=90:5:5), then adding 0.4 mol / L ammonia water and 1 mol / L sodium hydroxide aqueous solution into the first reaction kettle, adjusting the pH of the reaction system to 11.3, and obtaining a mixed solution;
[0063] S2, adding Al2O3, RuO2 and ethanol solution into the second reactor and mixing them evenly (wherein the molar ratio of elements Al:Ru:(Ni+Co+Mn)=0.02:0.02:1), then adding the mixed solution in S1 into the second reactor for coprecipitation reaction (the coprecipitation reaction is divided into the first stage and the second stage, the stirring speed of the first stage is 400rpm, the pH value of the reaction solution is 12.5, the ammonia value is 14g / L, and the reaction is 2.5h; the stirring speed of the second stage is 500rpm, the pH value of the reaction solution is 12.0, the ammonia value is 8g / L, and the reaction is 3h, and the ammonia value is the concentration of ammonia water) to obtain a solid-liquid mixture; then filtering, washing, drying, sieving, and demagnetizing the solid-liquid mixture to obtain a positive electrode material precursor, and the first and second stage reactions in the coprecipitation reaction can obtain precursors with different particle size distributions;
[0064] S3, the positive electrode material precursor in S2 and Li2CO3 (wherein the molar ratio of elements Li: (Ni + Co + Mn) = 1.08: 1) are mixed evenly, sintered at 750° C. for 13 h in an air atmosphere, and crushed to obtain a positive electrode active material; then the positive electrode active material is coated with alumina (Al2O3), tempered at 550° C., and sieved to obtain a positive electrode active material with a shell layer (wherein the mass fraction of the coating layer relative to the positive electrode active material is 0.02%);
[0065] S4, the positive electrode active material with a shell layer in S3, the conductive agent (conductive carbon black) and the binder (polyvinylidene fluoride) are mixed in a mass ratio of 97.3:1.8:0.9, and then mixed evenly with the solvent (N-methylpyrrolidone) to form a positive electrode slurry; then the positive electrode slurry is evenly coated on both sides of the positive electrode collector (aluminum foil) by a coating machine, and after drying, rolling, cutting, striping and other processes, the positive electrode sheet is obtained.
[0066] 2) The above-mentioned negative electrode sheet is prepared by the following preparation method:
[0067] The negative electrode active material (graphite), conductive agent (acetylene black), binder (styrene-butadiene rubber) and thickener (sodium carboxymethyl cellulose) are mixed in a mass ratio of 96:2:1:1, and then mixed evenly with deionized water to form a negative electrode slurry; then the negative electrode slurry is evenly coated on both sides of the negative electrode collector (copper foil) by a coating machine, and after drying, rolling, cutting, slitting and other processes, the negative electrode sheet is obtained.
[0068] Embodiments 2 to 5
[0069] Embodiments 2 to 5 provide a secondary battery, which is different from Embodiment 1 in that, during the preparation of the positive electrode sheet, the reaction time of the first stage and the second stage of the co-precipitation reaction in step S1 is adjusted to adjust the distribution density n1 of the first active particles in the positive electrode active layer, the distribution density n2 of the second active layer, and the volume ratio v1 / v2 of the first active particles to the second active particles per unit volume; at the same time, the rolling pressure during the preparation of the positive electrode sheet and the negative electrode sheet is adjusted to obtain a certain compaction of the positive electrode sheet and the negative electrode sheet, so that the porosity p1 of the positive electrode active layer and the porosity p2 of the negative electrode active layer are basically consistent with those in Embodiment 1.
[0070] Embodiment 6-7
[0071] Embodiments 6 and 7 provide a secondary battery, which is different from Embodiment 3 in that, during the preparation of the positive electrode sheet, the reaction time of the first stage and the second stage of the co-precipitation reaction in step S1 is adjusted so that the distribution density n1 of the first active particles in the positive electrode active layer, the distribution density n2 of the second active layer, and the volume ratio v1 / v2 of the first active particles and the second active particles per unit volume are basically consistent with those in Embodiment 3; at the same time, a positive electrode sheet with a certain compaction is obtained by adjusting the rolling pressure or the rolling gap parameters during the preparation of the positive electrode sheet to adjust the porosity p1 of the positive electrode active layer; and a negative electrode sheet with a certain compaction is obtained by adjusting the rolling pressure or the rolling gap parameters during the preparation of the negative electrode sheet, so that the porosity p2 of the negative electrode active layer is basically consistent with that in Embodiment 3.
[0072] Embodiments 8 to 11
[0073] Embodiments 8 to 11 provide a secondary battery, which is different from Embodiment 3 in that the reaction time of the first stage and the second stage of the co-precipitation reaction in step S1 of the positive electrode sheet preparation method is adjusted so that the distribution density n1 of the first active particles in the positive electrode active layer, the distribution density n2 of the second active layer, and the volume ratio v1 / v2 of the first active particles and the second active particles per unit volume are basically consistent with those in Embodiment 3; and the porosity p1 of the positive electrode active layer is basically consistent with that in Embodiment 3 by adjusting the rolling pressure or the rolling gap parameters in the process of preparing the positive electrode sheet; at the same time, the porosity p2 of the negative electrode active layer is adjusted by adjusting the rolling pressure or the rolling gap parameters in the process of preparing the negative electrode sheet.
[0074] Embodiments 12 to 13
[0075] Embodiments 12 and 13 provide a secondary battery. The difference between the secondary battery and embodiment 2 is that during the preparation of the negative electrode sheet, the particle size D is selected. v50 =3μm, particle size D v50 =12μm graphite is used as the negative electrode active material.
[0076] Embodiments 14 to 15
[0077] Embodiments 14 and 15 provide a secondary battery, which is different from Embodiment 2 in that, during the preparation of the negative electrode sheet, the compaction density of the negative electrode active layer is adjusted by adjusting the equipment pressure or the roller gap parameters during the rolling process.
[0078] Embodiments 16 to 17
[0079] Embodiments 16 and 17 provide a secondary battery, which is different from Embodiment 2 in that, during the preparation of the positive electrode plate, the value of W*h is adjusted by adjusting the amount of Al2O3 added in step S3.
[0080] Embodiments 18 to 19
[0081] Embodiments 18 and 19 provide a secondary battery, which is different from Embodiment 2 in that, during the preparation of the positive electrode plate, the aluminum oxide in step S3 is replaced by zirconium dioxide and titanium dioxide respectively to coat the positive electrode active material.
[0082] Comparative Examples 1-2
[0083] Comparative Examples 1 and 2 provide a secondary battery, which is different from Example 3 in that the reaction time of the first stage and the second stage of the co-precipitation reaction in step S1 of the positive electrode sheet preparation method is adjusted so that the distribution density n1 of the first active particles in the positive electrode active layer, the distribution density n2 of the second active layer, and the volume ratio v1 / v2 of the first active particles and the second active particles per unit volume are basically consistent with those in Example 3; and the porosity p1 of the positive electrode active layer is regulated by adjusting the rolling pressure or the rolling gap parameters in the process of preparing the positive electrode sheet; at the same time, the porosity p2 of the negative electrode active layer is adjusted by adjusting the rolling pressure or the rolling gap parameters in the process of preparing the negative electrode sheet.
[0084] Performance Testing
[0085] 1. Distribution density test of the first active particles and the second active particles in the positive electrode sheet
[0086] The cross-section of the positive electrode plate in each embodiment and comparative example is subjected to a scanning electron microscope test, and the SEM image (magnification of 1000 times) of the test sample is analyzed using the software or other tools with measurement functions, and the number of the first active particles (particle size ≥ 8μm) and the number of the second active particles (particle size <8μm) in the positive electrode active layer within the field of view are counted, and then the distribution density of the first active particles and the second active particles is calculated.
[0087] 2. Porosity test of positive and negative electrodes
[0088] Reference standards: GB / T 24533-2019 Graphite negative electrode materials for lithium-ion batteries; GB / T 33052-2016 Hexadecane absorption method in porosity determination method.
[0089] 3. Particle size D of negative electrode active material v50
[0090] Reference standard: GB-T 19077-2016 Particle size analysis laser diffraction method.
[0091] 4. Compaction density of negative electrode active layer
[0092] The thickness of the negative electrode sheet and the negative electrode current collector is measured by a precision spiral micrometer or a spiral ten-thousandth micrometer, the sheet is cut into small discs of a certain area, and the coating surface density of the negative electrode sheet is obtained after weighing using an analytical balance. The compaction density of the negative electrode active layer is calculated based on the thickness of the negative electrode sheet and the negative electrode current collector and the coating surface density of the negative electrode sheet.
[0093] 5. The thickness of the core surface shell in the positive electrode active material and the content of metal element X in the positive electrode active material
[0094] Method for testing the thickness of the inner core surface shell layer in the positive electrode active material: After preparing the positive electrode sample, perform TEM test to obtain a high-resolution transmission electron microscope photograph of the positive electrode active material, and analyze the surface and bulk structure based on the obtained high-resolution transmission electron microscope photograph to obtain the thickness data of the inner core surface shell layer in the positive electrode active material.
[0095] 6. Test method for the content of metal element X in positive electrode active materials
[0096] Refer to EPA 6010D-2018 for inductively coupled plasma atomic emission spectrometry.
[0097] Table 1 Parameters of the secondary batteries in the embodiments and comparative examples
[0098]
[0099] The units of n1 and n2 in Table 1 are pieces / 10000 μm 2 ; v1 / v2 is the volume ratio of the first active particles to the second active particles in the unit volume of the positive electrode active layer; w is the content of the metal element X (Al, Ti or Zr) in the positive electrode active material, in ppm; h is the thickness of the shell, in nm.
[0100] The electrical performance tests of the secondary batteries of the above-prepared embodiments and comparative examples were carried out as follows:
[0101] 1) 1 / 3C capacity test of secondary battery: place the secondary battery at a constant temperature of 25°C for 2h, charge to 4.25V at 1 / 3C within the voltage range of 2.8V to 4.25V, then charge at a constant voltage at 4.25V to a current ≤0.05mA, and place for 5min; then discharge to 2.8V at 1C; record the capacity of the secondary battery, and divide the capacity test value by the total mass of the secondary battery to obtain the capacity of the secondary battery at 1 / 3C.
[0102] 2) Cycle performance test of secondary batteries: Under a constant temperature of 45°C and a voltage range of 2.8V to 4.2V, first charge the secondary battery to 4.2V at a rate of 1C, then charge at a constant voltage at 4.2V to a current ≤0.05mA, and let stand for 5min; then discharge to 2.8V at 1C, and record the capacity as Dn (n=0, 1, 2, ...), repeat the previous process until the capacity decays to 80% of the initial capacity, and record the number of cycles of the secondary battery.
[0103] 3) High-temperature gas generation test of lithium-ion secondary batteries: After the secondary battery is fully charged to 4.25V at 1C, it is placed in a 70°C constant temperature box for 30 days; the initial volume of the battery and the volume after 30 days of standing are measured by the water displacement method, and the volume expansion rate of the secondary battery is calculated according to the following formula;
[0104] Volume expansion ratio (%) = (volume after standing for 30 days / initial volume - 1) × 100%.
[0105] 4) Fast charging performance test of lithium-ion secondary batteries: Under a constant temperature of 25°C and a voltage range of 2.8V to 4.2V, first charge the secondary battery to 4.2V at a rate of 1C, then charge at a constant voltage at 4.2V to a current ≤0.05mA, and let it stand for 5min; then discharge to 2.8V at 1C, repeat the previous process for 10 cycles, then disassemble the battery to observe the lithium deposition on the surface of the negative electrode. If no lithium deposition occurs, continue to increase the rate, and perform constant current charge and discharge tests on the battery at rate intervals of 1.5C, 1.8C, 2.1C, 2.4C, 2.7C, 3.0C..., and then disassemble and observe the lithium deposition on the surface of the negative electrode until obvious lithium deposition occurs on the negative electrode, and record the rate of the charge and discharge cycle after lithium deposition occurs.
[0106] Table 2 Performance of secondary batteries in various embodiments and comparative examples
[0107]
[0108]
[0109] The above test data shows that when the secondary battery meets 0.14≤Z≤4.67, Z=(n1 / n2)*(p1 / p2), the secondary battery has better cycle performance, safety performance and fast charging performance. Specifically, when the secondary battery meets the above conditions, the cycle life is greater than 1100 cycles, the volume expansion rate is less than 50% (reflecting that the battery has good safety performance), and the direct charging rate without lithium precipitation is higher than 2C.
[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A secondary battery, characterized in that: The invention comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer disposed on the surface of the positive electrode current collector, wherein the positive electrode active layer comprises a positive electrode active material; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector, wherein the negative electrode active layer comprises a negative electrode active material; The secondary battery satisfies: 0.14≤Z≤4.67; Where Z = (n1 / n2)*(p1 / p2); n1 / 10000μm 2 is the distribution density of the first active particles in the cross section of the positive electrode active layer, the first active particles being particles of the positive electrode active material particles having a size greater than or equal to 8 μm; n2 / 10000μm 2 is the distribution density of the second active particles in the cross section of the positive electrode active layer, wherein the second active particles are particles smaller than 8 μm in the positive electrode active material particles; p1 is the porosity of the positive electrode active layer; p2 is the porosity of the negative electrode active layer.
2. The secondary battery according to claim 1, wherein: The secondary battery satisfies: 1.24≤Z≤2.
43.
3. The secondary battery according to claim 1, wherein: The volume ratio of the first active particles to the second active particles per unit volume of the positive electrode active layer is 1:(0.3-0.6).
4. The secondary battery according to claim 1, wherein: 0.3≤n1 / n2≤7.
5. The secondary battery according to claim 1, wherein: Satisfy at least one of the following: a, n1 is 8 to 36; b. n2 is 6 to 25; c. p1 is 20% to 30%; d, p2 are 35%~45%.
6. The secondary battery according to claim 1, wherein: The negative electrode plate satisfies at least one of the following conditions: e. Particle size D of the negative electrode active material v50 3~12μm; f. The compaction density of the negative electrode active layer is 1.4 to 1.8 g / cm 3 .
7. The secondary battery according to claim 1, wherein: The positive electrode active material includes a core and a shell layer provided on the surface of the core, and the core includes a compound with the chemical formula Li 1+a [Ni x Co y Mn z M b O2; wherein, 0.5 ≤ x < 1, 0 < y < 0.3, 0 ≤ z < 0.3, -0.1 ≤ a < 0.2, 0 < b < 0.3, and x + y + z + b = 1; M includes at least one of Ti, Zr, Sr, Sb, Nb, Ru, Pd, Y, Ce, and W.
8. The secondary battery according to claim 7, characterized in that The content of the cobalt element increases gradually from the center of the core to the surface of the core.
9. The secondary battery according to claim 7, characterized in that: The shell layer includes a metal oxide, and the metal element X in the metal oxide includes at least one of Al, W, Ca, Ce, Ti, Zr, and Y.
10. The secondary battery according to claim 9, characterized in that The shell layer satisfies: 2500≤w*h≤16500; Wherein, w ppm is the content of the metal element X in the positive electrode active material, and h nm is the thickness of the shell layer.
11. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 1 to 10, wherein the secondary battery is used as a power supply for the electrical device.
Citation Information
Patent Citations
Cathode active material for secondary battery, preparation method therefor, and secondary battery comprising same
CN107408667A
Low cobalt positive electrode active material, method for preparing same, electrochemical device, and electronic apparatus
CN114835174A
Secondary battery and electric device comprising same
CN118970187A
Cited By
Secondary battery and electric device
CN120376720A